Synthesis and photodynamic antimicrobial chemotherapy against multi-drug resistant Proteus mirabilis of ornithine-porphyrin conjugates in vitro and in vivo - Meng, Shuai; Xu, Zengping; Wang, Xueming; Liu, Yang; Li, Bole; Zhang, Jie; Zhang, Xiaolong; Liu, Tianjun (Frontiers in Microbiology, 2023)
For the treatment of bacterial infections, photodynamic antimicrobial chemotherapy (PACT) has the advantage of circumventing multidrug resistance. In this work, new cationic photosensitizers against multi-drug resistant Proteus mirabilis (MRPM) were designed and synthesized by the conjugation of amino phenyl porphyrin with basic amino acid L-ornithine. Their photoinactivation efficacies against MRPM in vitro including the influence of laser energy, uptake, MIC and MBC, dose-dependent photoinactivation effects, membrane integrity and fluorescence imaging were reported. And the PACT in vivo was evaluated using a wound mice model infected by MRPM. Photosensitizer 4d displays high photo inactivation efficacy against MRPM at 7.81 µM under illumination, and it can accelerate wound healing via bactericidal effect. These ornithine-porphyrin conjugates are potential photosensitizers for PACT in the treatment of MRPM infection.